Longitudinal measures of RNA expression and disease activity in FSHD muscle biopsies. (21st February 2020) - Wong, Chao-Jen; Wang, Leo H; Friedman, Seth D; Shaw, Dennis; Campbell, Amy E; Budech, Chris B; Lewis, Leann M; Lemmers, Richard J F L; Statland, Jeffrey M; van der Maarel, Silvère M; Tawil, Rabi N; Tapscott, Stephen J
Abstract: Advances in understanding the pathophysiology of facioscapulohumeral dystrophy (FSHD) have led to the discovery of candidate therapeutics, and it is important to identify markers of disease activity to inform clinical trial design. For drugs that inhibit DUX4 expression, measuring DUX4 or DUX4-target gene expression might be an interim measure of drug activity; however, only a subset of FHSD muscle biopsies shows evidence of DUX4 expression. Our prior study showed that MRI T2-STIR-positive muscles had a higher probability of showing DUX4 expression than muscles with normal MRI characteristics. In the current study, we performed a 1-year follow-up assessment of the same muscle with repeat MRI and muscle biopsy. There was little change in MRI characteristics over the 1-year period and, similar to the initial evaluation, MRI T2-STIR-postive muscles had a higher expression of DUX4-regulated genes, as well as genes associated with inflammation, extracellular matrix and cell cycle. Compared to the initial evaluation, overall the level of expression in these gene categories remained stable over the 1-year period; however, there was some variability for each individual muscle biopsied. The pooled data from both the initial and 1-year follow-up evaluations identified several FSHD subgroups based on gene expression, as well as a set of genes—composed of DUX4-target genes, inflammatory and immune genes and cell cycle control genes—that distinguished all of the FSHD samples from the controls. These candidate markers of disease activity need to be replicated in independent datasets and, if validated, may provide useful measures of disease progression and response to therapy.